Assessment of Otomycosis and Frequency Distribution of Patients in Iraq - Qaysar Abdulwahhab suker alseaeadey; Majid Jalil Radhi; Qussy Khashan Majid Almajid (Genius Journals, 2022)
This study aims to Assessment of Otomycosis and Frequency Distribution of Patients in Iraq; and we were collected 50 patients from different Hospitals in Thi-Qar, Iraq, and the were divided into 35 men, and 15 women and this study targeted patients who suffer from Otomycosis The methodology of this study depends on taking a sample from the ear. The next step is to use 10% KOH for the purpose of culture of samples was performed on Saburo dextrose agar. Treatment of otomycosis is selected for each patient individually and depends on the type of fungal infection, as well as on the general condition of the body. The main goal is to get rid of the fungal infection and the factors that contribute to its development and exacerbation. Therefore, it is necessary to stop using antibiotics and ear drops (with a hormonal or antibacterial component) and to treat all diseases in a timely manner. Treatment should be aimed at preventing the development of complications, such as hearing loss perforation of the eardrum.
Keywords: KOH; otomycosis; ENT